Estimation of Available Phosphorus in Soil Using the Population of Arbuscular Mycorrhizal Fungi Spores - Machfud Effendy; Bhakti Wisnu Wijayani (JOURNAL OF TROPICAL SOILS, 2011)
Soil microbes, such as arbuscular mycorrhizal fungi (AMF) have the ability to dissolve unavailable phosphorus (P)  and they can be used as an indicator of the P availability in soil. The study was conducted on upland soil  in East Java. The soil  was sampled twice, before and after planting at the harvesting time. The population of AMF spores and soil P availability were observed. The AMF spores were isolated using wet sieving method, decanting, and followed by sucrose density gradient centrifugation. The available P was observed using the Olsen extraction. The numbers of AMF spore was corelated with available P, moreover the numbers of AMF spore was compared to the availabality of P.  The results showed that the total number of AMF spores at six sites were ranged from a little to midle, and the available P ranged from low to high level. All soil site samples had a linear corelation between numbers of AMF spore and  available P in soil.  The greater the number of AMF spore, the higher the available P in soil. It was likely that the availability of P in soil can be predicted by  the population of AMF spores in soil. Therefore, the number of AMF spore can be need as a biological method to predict the available P  in soil and to make a recommendation the use of P fertilizer.